2018
DOI: 10.1142/s1088424618500529
|View full text |Cite
|
Sign up to set email alerts
|

Redox switchable 19π and 18π 5,10,20-triaryl-5,15-diazaporphyrinoid–nickel(II) complexes

Abstract: The synthesis and optical, electrochemical, and magnetic properties of nickel(II) complexes of 5,10,20-triaryl-5,15-diazaporphyrin (TriADAP) are reported. Metal-templated cyclization of unsymmetrically substituted nickel(II)–bis(1-amino-9-chloro-5-mesityldipyrrin; mesityl = 2,4,6-trimethylphenyl) complexes afforded the corresponding TriADAPs or 5-aryl-15-benzyl-10,20-dimesityl-5,15-diazaporphyrin, depending on the combination of base and solvent. The latter macrocycle was converted to TriADAP by deprotection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…The redox potentials of TriAAOP were considerably shifted to the positive side (Δ E = 0.34‐0.36 V), compared with the corresponding potentials of TADAP. The observed results are in good accordance with the theoretically calculated results for their models (Figure ); the HOMO of 7‐m ( E = −4.56 eV) and LUMO of 9‐m ( E = −5.49 eV) are energetically stabilized compared with the corresponding orbitals of P0‐m ( E = −4.26 eV) and P2‐m ( E = −5.16 eV), respectively, at the same level of theory . These molecular orbitals have relatively large orbital coefficients at the meso ‐heteroatoms (vide supra) and therefore are markedly stabilized upon introducing the highly electronegative oxygen atom.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The redox potentials of TriAAOP were considerably shifted to the positive side (Δ E = 0.34‐0.36 V), compared with the corresponding potentials of TADAP. The observed results are in good accordance with the theoretically calculated results for their models (Figure ); the HOMO of 7‐m ( E = −4.56 eV) and LUMO of 9‐m ( E = −5.49 eV) are energetically stabilized compared with the corresponding orbitals of P0‐m ( E = −4.26 eV) and P2‐m ( E = −5.16 eV), respectively, at the same level of theory . These molecular orbitals have relatively large orbital coefficients at the meso ‐heteroatoms (vide supra) and therefore are markedly stabilized upon introducing the highly electronegative oxygen atom.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 5, TriAAOP exhibited two separate and reversible redox processes at −0.35 and +0.28 V (vs ferrocene/ferrocenium; Fc/Fc + ), which were attributed to , respectively, at the same level of theory. [25] These molecular orbitals have relatively large orbital coefficients at the meso-heteroatoms (vide supra) and therefore are markedly stabilized upon introducing the highly electronegative oxygen atom.…”
Section: Optical and Redox Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018, Matanosg roup reported that 19p neutral radicals (38R)b ased on 5,10,20triaryl-5,15-diazaporphyrins were quite stable. [57] Importantly, incorporation of one N-arylated amine-nitrogen unit altered the net charge of the p circuits of 5,15-diazaporphyrins, thereby making the 19p radical species stable enough to be isolated.…”
Section: Porphyrinoid-based and Other Macrocycle-based Radicalsmentioning
confidence: 99%
“…The presence of the meso ‐nitrogen atoms renders the redox properties of the 5,15‐diazaporphyrins flexible, which enables the isolation of stable 18π, 19π, and 20π species . In addition, cationic 5,15‐diazaporphyrin Ni II complexes with aryl groups at the meso ‐nitrogen atom have been prepared through one‐electron oxidation of 19π diazaporphyrin radicals …”
Section: Introductionmentioning
confidence: 99%